Minors' rights and solidarity among families regarding the custody of children - Bompiani, Adriano (Medicina e Morale, 1994)
The author dwells upon the inadequacy or pathology of the family that determine conditions of risk in bringing up children, after having briefly quoted the International Convention for children's rights (New York 1989, ratified by Italy with the act of May, 27, 1991, n. 176) regarding the promotion of temporary custody of minors to a different family. The article also points out the more frequent cases of juvenile deviance and transgression in modern society. In this framework the author estimates the contribution of custody of minors in recent ltalian experience since the Act on "Discipline of adoption and custody of minors" (May, 4, 1983, n. 184). The article describes positive aspects and difficulties of the correct enforcement of custody of minors, distortions due to the parties involved in the case, characteristics of juvenile judges' and social workers' current (frequent conflictual) outlooks, the area of responsibility of the social services and minors' court. The contribution dwells upon ethical aspects of custody of minors, which is of high moral content and inspired to solidarity, if it's correctly enforced. Finally, the author proposes the solution to the issues of the custody of minors and to promote the information regarding this law in society.